Dynamic Compression Mechanical Properties of TiZrHfX0.3 High‐Entropy Alloys. Issue 3 (3rd January 2023) - Chen, Chuang; Tu, Yiliang; Tang, Enling
Abstract : High‐entropy alloys (HEAs) are gradually replacing armor‐piercing core materials such as depleted uranium and tungsten alloys in high strain rate, high temperature, and high pressure service environments due to their excellent mechanical properties (high strength, high strain rate strengthening effect, and strong shear self‐sharpening characteristics). The dynamic compression performance of TiZrHf‐based HEAs with different elements, different strain rates, and multiple loadings is tested by the self‐constructed separate Hopkinson compression bar experimental system. The results show that the TiZrHfCu0.3 alloy has the largest elastic modulus and the strongest deformation resistance. TiZrHfAl0.3 and TiZrHfCu0.3 show a certain strain rate effect. The elastic modulus increases with the increase of loading times. The ultimate strength of TiZrHfAl0.3 remains unchanged after multiple loading, while the ultimate strength of TiZrHfCu0.3 and TiZrHfNi0.3 decreases gradually. Abstract : The effects of trace element types, strain rates, and multiple loading times on the dynamic compressive mechanical properties of TiZrHfAl0.3, TiZrHfCu0.3, and TiZrHfNi0.3 HEAs are studied. The alloys show a certain strain rate effect. The elastic modulus increases with the increase of loading times; the ultimate strength of TiZrHfCu0.3 and TiZrHfNi0.3 decreases gradually.